Women, Islam, and Abbasid identity - El-Cheikh, Nadia Maria (Harvard University Press, 2015)
When the Abbasids overthrew the Umayyads in 750 CE and ushered in Islam s Golden Age, ideas about gender and sexuality were central to the process by which the Caliphate achieved self-definition and articulated its systems of power and thought. Nadia Maria El Cheikh s study reveals the importance of women to the writing of early Islamic history.".